The Role of Grandparents in Shaping Faith Formation of Grandchildren: A Case Study - Deprez, Matthew Donald (Christian education journal, 2017)
Research has long suggested that the relationship between a grandparent and grandchild is one of the most critical and important relationships one will ever experience. Because of the importance of the grandparent-grandchild relationship, this article seeks to find how grandparents shape the faith formation of their grandchild, particularly looking at whether or not geographic proximity is a factor in their faith formation. We will begin by defining our problem statement and introductory thoughts, then move into a literature review synthesizing the findings from various research, articles, books, and publications that describe how grandparents shape the faith formation of their grandchild. Finally, we will examine the data analysis and results of our research before offering practical conclusions for grandparents and the church.